Innovative competences in public administration: The key to sustainable development, increasing financial efficiency and ensuring national security - Mykolaichuk, Mykola; Shpektorenko, Igor; Pershko, Larysa; Pasichnyi, Roman; Blishchuk, Kateryna; Dzvinchuk, Dmytro (Edelweiss Applied Science and Technology, 2024)
The definition and analysis of innovation in this article focus on how it may be interpreted as a dramatic shift in public administration that results in new goods, new technology, new procedures, and the introduction of new ideals. Novel paradigms, novel approaches to management, and novel kinds of innovation characterize modern public management models. A paradigm shift and the emergence of a new public management model built on innovative competences are discussed when innovation in public administration results in new operational approaches. The research is carried out within the paradigm of ‘hybridity’ as a key characteristic of today world and, accordingly, challenges for public administration. Ecosystem model, implying innovative competence in public administration, based on the pillars of hybrid- thinking and foresight paradigm, is suggested as the most corresponding to realities of today.